2006
DOI: 10.2478/v10001-006-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and Its Consequences in Healthcare Professionals: The Role of Type D Personality

Abstract: Modification of Type D personality aimed at reducing tendency to experience negative emotions and enhancing skills to express them combined with improving social relations is desired to prevent healthcare professionals from adverse health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 19 publications
9
117
0
5
Order By: Relevance
“…These can impact negatively on the healthcare worker's psychosocial wellbeing if not resolved in a satisfactory manner (Delobelle et al 2009;Mullins 2009;Van Dyk 2007). Some of the organisational challenges contributing to occupational stress or workplace-related stress include lack of space and privacy, insufficient organisational support and acknowledgement, heavy workload, inadequate training, insufficient funding, insufficient safety measures, and lack of medical supplies (Miller et al 2007;Mullins 2009;Ogińska-Bulik 2006).…”
Section: )mentioning
confidence: 99%
See 4 more Smart Citations
“…These can impact negatively on the healthcare worker's psychosocial wellbeing if not resolved in a satisfactory manner (Delobelle et al 2009;Mullins 2009;Van Dyk 2007). Some of the organisational challenges contributing to occupational stress or workplace-related stress include lack of space and privacy, insufficient organisational support and acknowledgement, heavy workload, inadequate training, insufficient funding, insufficient safety measures, and lack of medical supplies (Miller et al 2007;Mullins 2009;Ogińska-Bulik 2006).…”
Section: )mentioning
confidence: 99%
“…Although studies (such as Chirwa et al 2009;FredriksenGoldsen 2007;Ogińska-Bulik 2006;Van Dyk 2007) have shown dissatisfaction and dropout amongst AIDS care workers, caring for people living with HIV infection can provide significant satisfaction (Akintola 2008). Satisfaction takes the form of the caregiver's sense of doing a good deed, obtaining the patient's appreciation, or seeing improvement in the patient's condition (Moreno-Jiménez et al 2006).…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations